(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article delves in to the world of phraseological units, focusing specifically on those that denote feelings and emotions. Phraseological units are important elements of language that encapsulate complex emotions and cultural ideas in just a few words. The article looks at meaning, origins, and how we use common expressions like “all smiles”, “alive with joy”, “as happy as a lark”, “absolutely delighted”, “a burst of happiness”. Understanding these units enhance linguistic skills and deepens appreciation for the English language’s expressive capabilities.